Sexual Offences against Children Act 2017 (Act 792) - A Boost to Police Investigation and Prosecution - Mooi, Tan Geok; Awal, Noor Aziah Mohd (International Journal of Asian Social Science, 2020)
Sexual Offences against Children Act 2017 (Act 792) which came into force on 10 July 2017 has a significant impact on police investigation and prosecution. Hitherto the police relied on the Penal Code (Act) to investigate all children sexual abuse cases since there were no specific laws against the perpetration of child pornography, sexual grooming and other sexual abuses against children. Apparently not only does Act 792 confer extra powers upon the police to conduct investigation, it also simplifies the investigation and prosecution works of the police and Deputy Public Prosecutors respectively. This paper aims to examine Act 792 in relation to police investigation and prosecution since its implementation about two years ago. Its effectiveness is evaluated by comparing the overall cases investigated, charged in courts and convicted under this new statute. In addition, an analysis on the type of social media used to entice child victims in rape cases and age of the child victims are also conducted. This is a library-based qualitative research plus a face-to-face interview with a judge who presides over child sexual abuse cases. For conclusion, this paper makes some suggestions to improve the investigation, prosecution and also the Special Court for Child Sexual Crime which was launched on 22 June 2017 at the Palace of Justice, Putrajaya.